Докажите тождество:x^4-27x=x^2-3xx^2+3x+9

Докажите тождество:

x^4-27x=(x^2-3x)(x^2+3x+9)

  • x^4-27x=(x^2-3x)(x^2+3x+9)

  • x^4-27x=(x^2-3x)(x^2+3x+9)

    Доказательство:

    перемножим скобку на скобку, получим

    (x^2-3x)(x^2+3x+9) =
    х^4 + 3х^3 +9х^2 -3х^3-9х^2 -27х =

    отсюда сокращаются: 3х^3 минус 3х^3 и 9х^2 минус 9х^2;
    остаётся  х^4 - 27х.

    тождество доказано.

    ответ: x^4-27x=(x^2-3x)(x^2+3x+9)

  • (x^2-3x)(x^2+3x+9) перемножаем все

    х^4+3х^3+9х^2-3х^3-9^2-27х=х^4-27х